Makeup and Costumes in the Welcome Dance of Sri Maharaja Ligor - Ayu Wanda Sari; Dwi Agrita Putri; Naufal Zhoriffalah Chaniago (Yayasan Baru Haji Samsudin, 2024)
This research examines the makeup and costumes in the dance